Scaled-Down Biogas Production From Anaerobic Treatment Of Palm Oil Mill Effluent - Basri, Mohamad Firwance (2007)

(untitled)
This study is an extension of a 500 m3 methane recovery test plant study located at Serting Hilir Palm Oil Mill, Negeri Sembilan conducted by our research group on anaerobic treatment of palm oil mill effluent (POME). Biomass washout has become one of the problems faced by our research group because of the continuous mixing of effluent during anaerobic treatment of POME. Therefore, in this study, anaerobic POME treatment using a scaled down 50 L bioreactor which mimics the 500 m3 bioreactor was carried out to improve biogas production with and without biomass sedimentation. Three series of experiments were conducted under different conditions in terms of biomass sedimentation applied to the system. The first experiment was operated under semi-continuous mode whereas the second and third experiments were operated based on mix and settle mode system. As expected, by retaining biomass in the bioreactor, there was an improvement on the anaerobic process as the system from the second and third experiments were be able to operate at organic loading rate (OLR) of 3.5 and 6.0 kg COD/m3/d, respectively while the first experiment only achieved OLR of 3.0 kg COD/m3/d. At these OLR value, the hydraulic retention time (HRT) obtained was 10 days in the third experiment and followed by the first and second experiments with 15 days of HRT. The highest biogas production was achieved from the third experiment which was 2.42 m3/m3 of reactor/d. This was followed by second and first experiments which were 1.55 and 1.20 m3/m3 of reactor/d respectively. The highest methane production rate was also obtained in the third experiment with 0.992 m3/m3 of reactor/d as compared to the second and first experiments which were 0.655 and 0.553 m3/m3 of reactor/d, respectively. For COD removal, more than 90% of COD was removed for all of the experiments. The experimental data for the first experiment was applied to the two-stage mathematical model of acidogenesis and methanogenesis which were developed by previous researchers. The first experimental data was used because it represented the actual scenario on how the methane recovery test plant was operated in which biomass washout was taken into consideration. In modelling the behavior of the anaerobic digestion process, the mathematical model was used to simulate the methane production from the anaerobic treatment of POME. From the simulation result, the model was shown to be satisfactory for simulating methane production from the anaerobic treatment of POME.